2019
DOI: 10.1007/s10704-019-00398-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the displacement rate and inclination angle in steel fiber pullout tests

Abstract: This paper summarizes the results obtained in an experimental campaign on the effect of the displacement pullout rate and the inclination angle of the steel fiber pullout tests. For that purpose, specimens were obtained from a self-compacting concrete with a compressive strength of 86 MPa. In the experimental program, hooked-end steel fibers of 0.75 mm diameter and 60 mm length were used. Tests were executed with both hooked-end fibers, and smooth fibers obtained from the former by cutting the hooked end. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…To determine the tensile and compressive behavior of SFRC under impact load, it is important to consider that the fracture mechanism of this composite material varies with the loading rate, [43]. It is hypothesized that cracks in the matrix parts of SFRC start in the weaker interfacial transition zone (ITZ) between the aggregate and the matrix.…”
Section: Strain Rate Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the tensile and compressive behavior of SFRC under impact load, it is important to consider that the fracture mechanism of this composite material varies with the loading rate, [43]. It is hypothesized that cracks in the matrix parts of SFRC start in the weaker interfacial transition zone (ITZ) between the aggregate and the matrix.…”
Section: Strain Rate Effectmentioning
confidence: 99%
“…The fiber reinforcement performance depends on the strain rate, the geometry and the tensile strength of the fiber, [11]. In the range of quasi-static displacement rate, smooth fibers exhibit a clear dependency on displacement pullout rate, whereas hooked-end fibers can be considered largely insensitive to it, [43,44]. Under impact loading, hooked-end fibers are more prone to rupture when the strain rate is increased, [15].…”
Section: Strain Rate Effectmentioning
confidence: 99%
“…The contribution of each in the energy dissipation can vary, depending on the strain rate considered [49]. Moreover, some experimental studies [24,50] have investigated the effect of displacement rate in steel fiber pull-out test. They have shown that in the pull-out test, the rate sensitivity of the hooked end fibers is lower than the smooth fibers.…”
Section: Energy Absorption Capacity (Toughness)mentioning
confidence: 99%
“…They have shown that in the pull-out test, the rate sensitivity of the hooked end fibers is lower than the smooth fibers. Tarifa et al [50] reported that this behavior of hooked end fiber is caused by the prevalence of the anchorage provided by the hook over the physicochemical bond. It makes the viscous-elastic/plastic response of the concrete not completely develop, and consequently, the hooked end fibers have less sensitivity to the displacement rate.…”
Section: Energy Absorption Capacity (Toughness)mentioning
confidence: 99%
“…The free ends of the fibre were held by a grip (see Fig. 1c), further details of the experimental set-up can be found elsewhere (Tarifa et al 2019). Note that the tests regarding the slowest rate (0.01 mm/s) were obtained by Cunha (2010).…”
Section: Experimental Programmementioning
confidence: 99%